ICT Systems in reducing environmental impact – a way towards sustainability? - Lorek, Paweł (Systemy informatyczne jako instrument redukcji śladu środowiskowego – droga ku rozwojowi zrównoważonemu?, 2019)
The article discusses the issue of the evaluation of IT solutions in terms of sustainable development. Information systems manufacturers are increasingly showing interest in the market of pro-environmental services. The products they offer are to fit into the sector related to the reduction of energy intensity, renewable energy sources as well as waste management and recycling. However, there are many doubts about the benefits as well as the legitimacy of using such solutions. The article attempts a preliminary analysis of the potential benefits and problems that may occur using the example of a household energy consumption management system. The analysis takes into account the negative environmental and social effects that co-occur in the dissemination of IT solutions. These effects, often overlooked or not considered at all, constitute an important component of growth barriers for the entire ICT sector
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 1 (51), s. 35-43
Keywords: sustainable development; ICT systems; environmental impact; energy consumption; rozwój; systemy informatyczne; efekt środowiskowy; zużycie energii